2017
DOI: 10.1155/2017/7395032
|View full text |Cite
|
Sign up to set email alerts
|

Veronicastrum axillareAlleviates Ethanol-Induced Injury on Gastric Epithelial Cells via Downregulation of the NF-kB Signaling Pathway

Abstract: We used human gastric epithelial cells (GES-1) line in an ethanol-induced cell damage model to study the protective effect of Veronicastrum axillare and its modulation to NF-κB signal pathway. The goal was to probe the molecular mechanism of V. axillare decoction in the prevention of gastric ulcer and therefore provide guidance in the clinical application of V. axillare on treating injuries from chronic nephritis, pleural effusion, gastric ulcer, and other ailments. The effects of V. axillare-loaded serums on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Alcohol damages the stomach through NF-kB expression [ 6 , 42 ], a transcription factor that regulates the expression of inflammation and cell injury-associated genes [ 6 ]. In healthy resting cells, NF-kB in the cytosol is in an inactive form bound with inhibitor – kB (I-kB).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alcohol damages the stomach through NF-kB expression [ 6 , 42 ], a transcription factor that regulates the expression of inflammation and cell injury-associated genes [ 6 ]. In healthy resting cells, NF-kB in the cytosol is in an inactive form bound with inhibitor – kB (I-kB).…”
Section: Discussionmentioning
confidence: 99%
“…It is a signal pathway that plays a vital role in gastric ulcers and gastric pathology through involvement in multitudes of actions. The activation of NF-kB results in the up-regulated expression of many mediators of inflammation [ 6 , 42 ]. The exposure of rats to ethanol in our study also resulted in overexpression of NF-kB compared to the control animals, while pretreatment with different TPM doses markedly down-regulated the overexpression of NF-kB ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The oxidative stress that leads to the production of reactive oxygen species (ROS) along with the decline in antioxidative enzymes at the gastric mucosa induced by ethanol ingestion is implicated in the pathogenesis of ethanol-induced gastric ulceration [ 5 ]. Alcohol consumption induces gastric mucosal damage and apoptosis through tumor necrosis factor- α (TNF- α ) signaling and ROS formation [ 6 ]. TNF- α , an initiating proinflammatory cytokine, has a critical role in the pathogenesis of gastric ulcer via inflammation and injury inducement [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many previous studies illustrated that the NF-κB activation led to an elevation in the expression of many inflammatory mediators that were all implicated in the pathogenesis of peptic ulcer (Ajayi and Olaleye 2020 ; Raish et al 2021 ; Sidahmed et al 2013 ; Su et al 2017 ; Zhao et al 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…The most obvious effect was seen in the AB-B EOtreated group at a 200 mg/kg dose that was not significantly different from ranitidine (used as a standard drug). It was previously reported that inhibiting the NF-κB and its downstream targets had a role in the healing of peptic ulcers (Zhao et al 2017). Furthermore, it had been illustrated before that the crude EO of the Egyptian A. heterophylla at a dose of 200 mg/kg reduced the levels of proinflammatory cytokines (TNF-α, IL-6, and IL-1β), paw edema, and rectal temperature in a carrageenan-induced rat model (Elshamy et al 2020a, b).…”
Section: Anti-helicobacter Pylori Activitymentioning
confidence: 99%